Environment-friendly SiO2 gas gel paste and preparation method thereof

By using silane-treated chopped fibers and surface modification technology in SiO2 gas gel, the problems of cumbersome preparation of SiO2 gas gel materials and the prone to powder loss and crushing during application are solved, and the mechanical properties are improved, the material applicability and hydrophobic insulation properties are enhanced.

CN119569417APending Publication Date: 2025-03-07HEU SHIP EQUIP & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411787086.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing SiO2 gas gel materials are cumbersome in preparation, harsh drying conditions, easy to lose powder, crush, difficult to replace, and gaps with special-shaped parts during application.

Method used

The environmentally friendly SiO2 gas gel paste was prepared by using silane-treated chopped fibers as the reinforced phase.

Benefits of technology

It improves the mechanical properties of SiO2 gas gel paste, avoids powder loss and crushing problems, simplifies the preparation and drying process, is suitable for application on special-shaped parts, and enhances the applicability of the material and the hydrophobic insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569417A_ABST
    Figure CN119569417A_ABST
Patent Text Reader

Abstract

The invention discloses environment-friendly SiO2 gas gel paste and a preparation method thereof, and belongs to the technical field of porous materials. The problems that in the prior art, a SiO2 aerogel material is tedious in preparation and harsh in drying condition, powder is broken and falls off in the application process, and replacement is difficult are solved. The fiber is used as a reinforcing phase and is compounded with the SiO2 gas gel through polymerization aging, replacement, hydrophobic modification and other reactions, the mechanical property of the SiO2 gas gel is improved on the basis that the SiO2 gas gel has hydrophobicity, dust is not generated in the application process, the SiO2 gas gel is not prone to being smashed and easy to replace, in addition, the SiO2 gas gel paste is simple in preparation process, strict drying conditions are not needed, and the preparation process is simple. The preparation method of the SiO2 gas gel paste provided by the invention comprises the following steps: (1) preparing SiO2 wet gel; (2) polymerizing and aging; (3) solvent replacement; (4) surface modification; and (5) filtering and drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous materials, and in particular relates to an environmentally friendly SiO2 gas gel paste and a preparation method thereof. Background Art

[0002] SiO2 aerogel has a nano-space network porous structure, extremely low density, ultra-high specific surface area, and very low thermal conductivity. These excellent properties make SiO2 aerogel have application prospects in many aspects. However, with the diversification of application conditions, the requirements for the processing performance of SiO2 aerogel are getting higher and higher. The existing SiO2 aerogel is usually prepared by the sol-gel method. The prepared SiO2 aerogel has the characteristics of high porosity and small pore size, and the porous structure is composed of aggregates of silicon dioxide nanoparticles. However, SiO2 aerogel is brittle, has poor toughness, is not easy to bend, has poor mechanical properties, and is easy to break, which makes it very unstable during application, easy to lose powder or even break. In order to improve the mechanical properties of SiO2 aerogel, SiO2 aerogel is usually combined with other substances to make SiO2 aerogel composite materials, such as SiO2 aerogel and glass fiber felt are compounded into SiO2 aerogel felt, but the reinforcing phase still cannot improve the mechanical properties of SiO2 aerogel well. During the application process, a large amount of powder will still fall off when the aerogel felt is wrapped, fixed or disassembled, which not only pollutes the environment but also causes certain harm to the human body. Especially in the pipeline system, when encountering special-shaped parts, due to the certain hardness of SiO2 aerogel felt, it is difficult to make it fit tightly with special-shaped parts such as valves, so gaps are generated, which causes a large amount of heat loss to the insulation system, reducing the thermal insulation of the material.

[0003] In addition, the preparation method of the enhanced SiO2 aerogel material has certain defects. At present, many technicians have conducted research on this. Chinese patent CN101973752B provides a preparation method of a glass fiber reinforced silica composite material. The aerogel is prepared on the basis of a secondary modified aerogel process to obtain a silica aerogel composite material. The composition of the composite material includes silica aerogel and reinforcing fibers. After the gel is formed, a block composite aerogel material is obtained through aging, modification, drying and other steps. Although this method can improve the performance of aerogel to a certain extent, the gradient temperature drying method used limits the construction conditions of aerogel in the actual production process, and the formed block aerogel composite material also limits the application range of aerogel. German patents DE-A-4430669 and DE-A-4430642 provide fiber-reinforced aerogel plates or mats. Due to the high aerogel content, the thermal conductivity of these plates or mats is very low, but due to the slow diffusion of the solvent, the production of fiber-reinforced aerogel plates or mats requires a long period of time. It can be seen that at present, enhanced SiO2 aerogel materials cannot be widely produced due to the complicated preparation process and strict drying conditions, such as supercritical drying and freeze drying.

[0004] Therefore, it is necessary to develop a SiO2 gas gel material with simple preparation method and drying conditions, and no problems such as powder loss, breakage, falling off, difficulty in replacement, and gaps with special-shaped parts during application. Summary of the invention

[0005] In order to solve the problems of complicated preparation of SiO2 aerogel materials in the prior art, harsh drying conditions, powder loss, breakage and falling off during application, difficulty in replacement, and gaps with special-shaped parts, the present invention provides an environmentally friendly SiO2 aerogel paste and a preparation method thereof.

[0006] The technical solution of the present invention:

[0007] One of the purposes of the present invention is to provide a method for preparing an environmentally friendly SiO2 aerogel paste, comprising:

[0008] (1) Preparing SiO2 wet gel: dissolving a silicon source in deionized water and stirring to obtain a sodium silicate aqueous solution, then adding urea, imidazole carboxylic acid ionic liquid, functional filler, dispersant, and sunscreen to obtain a mixed solution, stirring the mixed solution, stopping stirring when the mixed solution shows signs of thickening, adding fibers treated with a silane coupling agent, and stirring to obtain SiO2 wet gel with fibers;

[0009] (2) Polymerization aging: The SiO2 wet gel with fibers is moved to another container for polymerization aging;

[0010] (3) Solvent replacement: The SiO2 wet gel with fibers after polymerization aging is washed and then subjected to a replacement reaction;

[0011] (4) Surface modification: The SiO2 wet gel with fibers after the replacement reaction is filtered, the material obtained after the filtration is placed in n-hexane for mechanical stirring, and then a hydrophobic agent is added to perform surface hydrophobic modification to obtain a super-hydrophobic SiO2 wet gel fiber system;

[0012] (5) Filtration and drying: The superhydrophobic SiO2 wet gel fiber system is filtered and washed with n-hexane, and then dried to obtain a SiO2 gas gel paste.

[0013] Further defined, the structural formula of the imidazole carboxylic acid ionic liquid is:

[0014]

[0015] Where R is C 1~10 A straight chain alkane group.

[0016] It is further defined that the silicon source in (1) is 3.1 mode water glass or tetraethyl orthosilicate.

[0017] It is further defined that the functional filler in (1) is TiO2, talc or sepiolite.

[0018] It is further defined that the dispersant in (1) is 602N dispersant or OS-5040 dispersant.

[0019] It is further defined that the sunscreen in (1) is a styrene-acrylate copolymer.

[0020] It is further defined that the silane coupling agent in (1) is KH-560.

[0021] It is further defined that the fiber in (1) is one or both of glass chopped fibers and ceramic chopped fibers.

[0022] It is further defined that the fiber length in (1) is 2.2 to 3.0 mm.

[0023] It is further defined that in (1), by weight, the amount of silicon source is 40 to 100 parts, the amount of deionized water is 160 to 400 parts, the amount of urea is 10 to 20 parts, the amount of carboxylic acid ionic liquid is 100 to 200 parts, the amount of functional filler is 5 to 40 parts, the amount of dispersant is 5 to 10 parts, the amount of sunscreen is 0 to 20 parts, and the amount of fiber treated with silane coupling agent is 50 to 100 parts.

[0024] It is further defined that the polymerization aging temperature in (2) is 70°C and the time is 8 hours.

[0025] It is further defined that the replacement reaction time in (3) is 16 to 72 hours.

[0026] It is further defined that the solution for the replacement reaction in (3) is a mixture of anhydrous ethanol and tetraethyl orthosilicate or anhydrous ethanol.

[0027] It is further defined that the hydrophobic agent in (4) is trimethylchlorosilane or hexamethyldisilazane.

[0028] It is further defined that the amount of the hydrophobic agent in (4) is 0 to 40 parts by weight.

[0029] It is further defined that the mechanical stirring speed in (4) is 800 r / min.

[0030] It is further defined that the drying temperature in (5) is 60° C. and the drying time is 2 to 6 hours.

[0031] The second object of the present invention is to provide an environmentally friendly SiO2 gas gel paste obtained by the above preparation method.

[0032] The beneficial effects of the present invention are:

[0033] The SiO2 aerogel paste prepared by the present invention is an environmentally friendly SiO2 aerogel and fiber composite material in a paste form. Compared with the prior art, the present invention has the following advantages:

[0034] (1) The present invention uses silane-treated short-cut fibers as a reinforcing phase. In the SiO2 aerogel paste, the fibers serve as a skeleton to reduce the damage to the network structure of the aerogel by stress, thereby improving the mechanical properties of the SiO2 aerogel paste. In addition, the fibers used in the present invention are short-cut fibers. Such fibers are discontinuous inside the aerogel and have better dispersion, thereby maintaining the stability of the material and further improving the mechanical properties of the SiO2 aerogel paste. At the same time, the present invention treats the fibers with a silane coupling agent, and introduces hydroxyl groups on the fibers to cause a condensation reaction with the hydroxyl groups on the surface of the SiO2 aerogel. The connection strength between the fibers and the aerogel is further enhanced to achieve the purpose of enhancing the mechanical properties, thereby improving the problems of strong brittleness, poor toughness, difficulty in bending, and poor mechanical properties, so that the material is not easy to fall into powder or break during use.

[0035] (2) The acidic medium of the present invention is a carboxylic acid ion liquid, which avoids the environmental pollution caused by using acetic acid as the acidic medium in the traditional method, and is green and environmentally friendly; in the method provided by the present invention, the functional filler enables the SiO2 gas gel to maintain good porous network structure characteristics, which is beneficial to the stable composite of the SiO2 gas gel and the fiber, as well as various reactions such as polymerization aging, solvent replacement, and modification.

[0036] (3) The network pore structure of SiO2 aerogel, which is constructed by silicon-oxygen bonds (Si-O-Si), depends on the degree of hydrolysis and polycondensation of the precursor. Carboxylic acid ionic liquids are not only environmentally friendly but also mildly acidic. They can promote the hydrolysis and polycondensation of the precursor, generate more mesoporous structures, reduce capillary forces, and make the SiO2 aerogel have a higher porosity. The structure of the SiO2 skeleton is optimized, so that the material can better disperse stress during stretching, thereby improving the tensile properties of the SiO2 aerogel paste. At the same time, the optimized SiO2 skeleton structure is conducive to maintaining the stability of the aerogel pores, making the SiO2 aerogel more susceptible to hydrophobic modification and making the material hydrophobic. In addition, the high porosity of the SiO2 aerogel means that there are a large number of nanopores inside it. These pores can provide a large number of positions for short fibers, increase the contact area between the fibers and the SiO2 aerogel, and better combine the fibers with the aerogel, further improving the mechanical properties of the SiO2 aerogel paste.

[0037] (4) SiO2 aerogel materials often require aerogels with specific shapes during their application. However, the production cycle of aerogel materials with specific shapes is prolonged due to limited solvent, diffusion-determined solvent exchange and drying. However, the method provided by the present invention can shape the composite material after the aerogel composite material is prepared, that is, after drying, without changing the internal structure of the aerogel and without reducing the mechanical properties of the aerogel.

[0038] (5) After reinforcement, conventional SiO2 aerogel materials are mostly solids with a specific shape, or solids with high hardness and difficult to change shape, such as felt. They are not only prone to generate dust during application, but also have poor compatibility with special-shaped parts. The SiO2 aerogel material of the present invention is a paste. Not only does it not generate dust during application, it solves the problems in the application and construction process, but it can also be well applied to special-shaped parts. The aerogel paste can be coated on the special-shaped parts at one time to a certain thickness, and there is no gap between the special-shaped parts, which improves the applicability of the material. Moreover, when the SiO2 aerogel paste of the present invention is used in a thermal insulation system, heat loss can be avoided to ensure hydrophobic thermal insulation performance.

[0039] (6) The preparation method provided by the present invention can prepare SiO2 gas gel paste at room temperature and pressure. The equipment is simple and energy-saving. The drying step is simple and does not require excessively high temperature and complicated conditions. The prepared SiO2 gas gel paste maintains stable size after a simple drying step and has a certain hydrophobicity and improved mechanical properties. It can be painted, constructed, and replaced at room temperature. No dust is generated during the application process. It is both environmentally friendly and has a certain hydrophobicity.

[0040] (7) The SiO2 aerogel paste of the present invention not only does not generate dust during application, thus solving the problems encountered during construction, but can also be well applied to special-shaped parts. The aerogel paste can be coated on the special-shaped parts to a certain thickness at one time, leaving no gap between the special-shaped parts, thereby improving the applicability of the composite material. Furthermore, when the composite material of the present invention is used in thermal insulation materials, heat loss can be avoided, thereby ensuring the hydrophobic thermal insulation performance of the aerogel.

[0041] (8) When the SiO2 gas gel paste of the present invention needs to be disassembled after long-term use, it is easy to scrape off without encountering powder falling off during scraping, and it will not remain on the device, thereby avoiding secondary dust pollution to the environment and harm to human health. The molded product is both environmentally friendly and beautiful, saving production time.

[0042] (9) The SiO2 aerogel paste of the present invention may contain a sunscreen. The fine nano-network structure inside the SiO2 aerogel makes the aerogel have low solid and gaseous thermal conductivity. When the paste is used for exterior wall insulation, the aerogel is transparent to infrared radiation in the band of 2 to 8 μm. Under high temperature conditions, the thermal radiation energy in this band all passes through the aerogel, which will cause the thermal conductivity of the aerogel to rise sharply. The present invention adds a sunscreen that can absorb or scatter infrared light to the SiO2 aerogel paste, thereby reducing the radiation heat rate of the aerogel, thereby making the application scope and prospects of the SiO2 aerogel paste more extensive. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a scanning electron microscope photograph of the aerogel paste prepared in Example 1 (magnification 500x);

[0044] Figure 2 This is a scanning electron microscope photograph of the aerogel paste prepared in Example 1 (magnification 10000x);

[0045] Figure 3 This is a photograph of the hydrophobic angle of the aerogel paste prepared in Example 1;

[0046] Figure 4 This is the tensile curve of the aerogel paste product after molding obtained in Example 1. DETAILED DESCRIPTION

[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0048] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0049] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0050] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0051] Example 1

[0052] The preparation method of the environmentally friendly SiO2 aerogel paste provided in this embodiment is as follows:

[0053] (1) Preparation of SiO2 wet gel: 40 g of water glass (modulus 3.1) as a silicon source was dissolved in 160 g of deionized water, and magnetic stirring was performed at a speed of 700 r / min at room temperature and pressure until the water glass was completely dissolved to obtain a transparent sodium silicate aqueous solution. Then, 10 g of urea, 100 g of imidazole carboxylic acid ionic liquid, and 10 g of TiO2 (specific surface area 55 m 2 / g), 5g Akzo 602N dispersant (purchased from Nouryon), 3g Dow OP301 sunscreen, stirred at a speed of 1000r / min to mix evenly, stopped stirring when the liquid showed signs of thickening, quickly put in 50g of chopped glass fibers with a length of 2.2 to 3.0mm treated with silane coupling agent KH-560, then stirred at a speed of 800r / min to mix evenly, stopped stirring when the mixed liquid showed further thickening and difficulty in stirring, and obtained SiO2 wet gel with glass fibers. In this process, urea and imidazole carboxylic acid ionic liquid play a catalytic role, and the structure of imidazole carboxylic acid ionic liquid is as follows:

[0054]

[0055] Wherein, R is a methyl group;

[0056] The method for treating glass fiber with silane coupling agent KH-560 is as follows: heat-treating short glass fiber at 110°C for 30 minutes, then adding the short glass fiber into a mixed solution of KH-560 and anhydrous ethanol, wherein the weight ratio of KH-560 to anhydrous ethanol is 1:4, stirring for 3 hours, and then drying and taking out for standby use, wherein the amount of KH-560 is 1% of the mass of the glass fiber;

[0057] (2) Polymerization aging: The SiO2 wet gel with glass fiber was moved into a reactor and polymerized and aged at 70°C for 8 h;

[0058] (3) Solvent replacement: The aged SiO2 wet gel with glass fibers was washed with deionized water and then placed in 210 g of anhydrous ethanol for replacement for 16 h;

[0059] (4) Surface modification: The SiO2 wet gel system with glass fibers obtained after the replacement in (3) was filtered, placed in n-hexane, and mechanically stirred at 800 r / min for 30 min. Then, 2 g of hexamethyldisilazane (HMDZ) was added at room temperature to perform surface hydrophobic modification on the SiO2 wet gel system with glass fibers. The mixture was stirred and dissolved, and the SiO2 wet gel system was immersed in the mixed solution for 24 h to complete the hydrophobic modification and obtain a super-hydrophobic SiO2 wet gel glass fiber system.

[0060] (5) Filtration and drying: After the modified super-hydrophobic SiO2 wet gel glass fiber system is filtered, it is immersed in n-hexane for 24 hours, and then washed with n-hexane. After washing, it is dried at 60°C for 6 hours to obtain a fiber-reinforced super-hydrophobic SiO2 gas gel paste, which is finally sealed and stored.

[0061] Example 2

[0062] The difference between this embodiment and embodiment 1 is that: the amount of TiO2 functional filler used in (1) is 5g, and the remaining steps and process parameters are the same as those in embodiment 1.

[0063] Example 3

[0064] The difference between this embodiment and embodiment 1 is that the amount of hexamethyldisilazane used in (1) is 4 g, and the remaining steps and process parameters are the same as those in embodiment 1.

[0065] Example 4

[0066] (2) Preparation of SiO2 wet gel: 100 g of water glass (modulus 3.1) as a silicon source was dissolved in 400 g of deionized water, and magnetic stirring was performed at a speed of 700 r / min at room temperature and pressure until the water glass was completely dissolved to obtain a transparent sodium silicate aqueous solution. Then, 15 g of urea, 150 g of imidazole carboxylic acid ionic liquid, and 40 g of talc (specific surface area 35 m 2 / g), 10g dispersant OS-5040, 20g Dow OP301 sunscreen, stir and mix at a speed of 1000r / min, stop stirring when the liquid shows signs of thickening, quickly add 100g glass fiber with a length of 2.2-3.0mm treated with silane coupling agent KH-560, then stir at a speed of 800r / min to mix evenly, stop stirring when the mixed liquid becomes thicker and difficult to stir, and obtain SiO2 wet gel with glass fiber. In this process, urea and imidazole carboxylic acid ionic liquid play a catalytic role. The structure of imidazole carboxylic acid ionic liquid is as follows:

[0067]

[0068] Wherein, R is a methyl group;

[0069] The method for treating glass fiber with silane coupling agent KH-560 is as follows: heat-treating short glass fiber at 110°C for 30 minutes, then adding the short glass fiber into a mixed solution of KH-560 and anhydrous ethanol, wherein the weight ratio of KH-560 to anhydrous ethanol is 1:4, stirring for 3 hours, and then drying and taking out for standby use, wherein the amount of KH-560 is 1% of the mass of the glass fiber;

[0070] (2) Polymerization aging: The SiO2 wet gel with glass fiber was moved into a reactor and polymerized and aged at 70°C for 8 h;

[0071] (3) Solvent replacement: The aged SiO2 wet gel with glass fibers was washed with deionized water and then placed in 210 g of anhydrous ethanol for 72 h;

[0072] (4) Surface modification: The wet gel system with glass fibers obtained after the replacement in (3) was filtered, placed in n-hexane, and mechanically stirred at 800 r / min for 30 min. Then, 40 g of hexamethyldisilazane (HMDZ) was added at room temperature to hydrophobically modify the surface of the wet gel system with glass fibers. The mixture was stirred and dissolved, and the SiO2 wet gel system was immersed in the mixed solution for 24 h to complete the hydrophobic modification and obtain a hydrophobic SiO2 wet gel glass fiber system.

[0073] (5) Filtration and drying: After the modified SiO2 wet gel glass fiber system is filtered, it is immersed in n-hexane for 24 hours, and then washed with n-hexane. After washing, it is dried at 60°C for 6 hours to obtain a fiber-reinforced superhydrophobic SiO2 gas gel paste, which is finally sealed and stored.

[0074] Example 5

[0075] (3) Preparation of SiO2 wet gel: 70 g of water glass (modulus 3.1) as a silicon source was dissolved in 280 g of deionized water, and magnetic stirring was performed at a speed of 700 r / min at room temperature and pressure until the water glass was completely dissolved to obtain a transparent sodium silicate aqueous solution. Then, 20 g of urea, 200 g of imidazole carboxylic acid ionic liquid, and 30 g of sepiolite (specific surface area 440 m 2 / g), 7.5g dispersant OS-5040, 10g Dow OP301 sunscreen, stirred at a speed of 1000r / min to mix evenly, stopped stirring when the liquid showed signs of thickening, quickly put in 75g of glass fiber with a length of 2.2-3.0mm treated with silane coupling agent KH-560, then stirred at a speed of 800r / min to mix evenly, stopped stirring when the mixed liquid showed further thickening and difficulty in stirring, and obtained SiO2 wet gel with glass fiber. In this process, urea and imidazole carboxylic acid ionic liquid play a catalytic role, and the structure of imidazole carboxylic acid ionic liquid is as follows:

[0076]

[0077] Wherein, R is a methyl group;

[0078] The method for treating glass fiber with silane coupling agent KH-560 is as follows: heat-treating short glass fiber at 110°C for 30 minutes, then adding the short glass fiber into a mixed solution of KH-560 and anhydrous ethanol, wherein the weight ratio of KH-560 to anhydrous ethanol is 1:4, stirring for 3 hours, and then drying and taking out for standby use, wherein the amount of KH-560 is 1% of the mass of the glass fiber;

[0079] (2) Polymerization aging: The SiO2 wet gel with glass fiber was moved into a reactor and polymerized and aged at 70°C for 8 h;

[0080] (3) Solvent replacement: The aged SiO2 wet gel with glass fibers was washed with deionized water and then placed in 210 g of anhydrous ethanol for 44 h;

[0081] (4) Surface modification: The wet gel system with glass fibers obtained after the replacement in (3) was filtered, placed in n-hexane, and mechanically stirred at 800 r / min for 30 min. Then, 20 g of hexamethyldisilazane (HMDZ) was added at room temperature to hydrophobically modify the surface of the wet gel system with glass fibers. The mixture was stirred and dissolved, and the SiO2 wet gel system was immersed in the mixed solution for 24 h to complete the hydrophobic modification and obtain a hydrophobic SiO2 wet gel glass fiber system.

[0082] (5) Filtration and drying: After the modified SiO2 wet gel glass fiber system is filtered, it is immersed in n-hexane for 24 hours, and then washed with n-hexane. After washing, it is dried at 60°C for 6 hours to obtain a fiber-reinforced superhydrophobic SiO2 gas gel paste, which is finally sealed and stored.

[0083] Example 6

[0084] (4) Preparation of SiO2 wet gel: 50g of water glass (modulus 3.1) as a silicon source was dissolved in 200g of deionized water, and magnetically stirred at a speed of 700r / min at room temperature and pressure until the water glass was completely dissolved to obtain a transparent sodium silicate aqueous solution, and then 10g of urea, 200g of imidazole carboxylic acid ionic liquid, 5g of TiO2, 5g of dispersant Aksu 602N, and 15g of Dow OP301 sunscreen were added, and stirred and mixed at a speed of 1000r / min. When the liquid showed signs of thickening, stirring was stopped, and 750g of glass fiber with a length of 2.2 to 3.0mm treated with silane coupling agent KH-560 was quickly added, and then stirred and mixed at a speed of 800r / min to obtain a SiO2 wet gel with glass fiber. In this process, urea and imidazole carboxylic acid ionic liquid play a catalytic role. The structure of imidazole carboxylic acid ionic liquid is as follows:

[0085]

[0086] Wherein, R is a methyl group;

[0087] The method for treating glass fiber with silane coupling agent KH-560 is as follows: heat-treating short glass fiber at 110°C for 30 minutes, then adding the short glass fiber into a mixed solution of KH-560 and anhydrous ethanol, wherein the weight ratio of KH-560 to anhydrous ethanol is 1:4, stirring for 3 hours, and then drying and taking out for standby use, wherein the amount of KH-560 is 1% of the mass of the glass fiber;

[0088] (2) Polymerization aging: Place the SiO2 wet gel with glass fiber into 200 g of anhydrous ethanol solution, cover with plastic wrap and let stand for aging. The aging time at room temperature is 48 h.

[0089] (3) Solvent replacement: The aged SiO2 wet gel with glass fibers was washed with deionized water and then placed in 210 g of anhydrous ethanol for 48 h;

[0090] (4) Surface modification: The wet gel system with glass fibers obtained after the replacement in (3) was filtered, placed in n-hexane, and mechanically stirred at 800 r / min for 30 min. Then, 2 g of hexamethyldisilazane (HMDZ) was added at room temperature to perform surface hydrophobic modification on the wet gel system with glass fibers. The mixture was stirred and dissolved, and the SiO2 wet gel system was immersed in the mixed solution for 24 h to complete the hydrophobic modification and obtain a hydrophobic SiO2 wet gel glass fiber system.

[0091] (5) Filtration and drying: After the modified SiO2 wet gel glass fiber system is filtered, it is immersed in n-hexane for 24 hours, and then washed with n-hexane. After washing, it is dried at 60°C for 6 hours to obtain a fiber-reinforced superhydrophobic SiO2 gas gel paste, which is finally sealed and stored.

[0092] Characterization and performance testing

[0093] (I) Performance test

[0094] 1. Test of the actual drying time of fiber-reinforced superhydrophobic SiO2 aerogel paste at room temperature

[0095] When the SiO2 aerogel paste provided by the present invention is used on a special-shaped part, the coating thickness thereof is different and the time required for the paste to dry is different, as shown in Table 1.

[0096] Table 1 The time required for the SiO2 aerogel paste prepared in Examples 1 to 6 to dry at different coating thicknesses

[0097]

[0098] 2. Performance test of superhydrophobic fiber reinforced superhydrophobic SiO2 aerogel paste

[0099] The fiber-reinforced super-hydrophobic SiO2 aerogel paste provided by the present invention has different performance parameters of the obtained SiO2 aerogel paste when the functional filler and the hydrophobic agent are used in different proportions, as shown in Table 2 and Table 3.

[0100] Table 2 Performance test results of fiber-reinforced super-hydrophobic SiO2 aerogel paste prepared with different functional fillers and hydrophobic agent ratios (coating thickness: 3 mm)

[0101] Example 1 2 3 5 Coating thickness(mm) 3 3 3 3 Thermal conductivity W / (m·K) 0.064 0.068 0.070 0.063 Hydrophobic angle (°) 128.8 134.2 135.2 140.3 Drying time at room temperature (h) 3 3 3 3

[0102] Table 3 Performance test results of fiber-reinforced super-hydrophobic SiO2 aerogel paste prepared with different functional fillers and hydrophobic agent ratios (coating thickness: 5 mm)

[0103] Example 1 2 4 6 Coating thickness(mm) 5 5 5 5 Thermal conductivity W / (m·K) 0.064 0.063 0.065 0.063 Hydrophobic angle (°) 129.3 137 126.7 138.9 Drying time at room temperature (h) 7 7 7 7

[0104] (II) Characterization and observation

[0105] 1. Microscopic morphology observation

[0106] Figure 1 This is a scanning electron microscope image of the fiber-reinforced super-hydrophobic SiO2 aerogel paste prepared in Example 1, magnified 500 times. Figure 1 It can be seen that the chopped glass fibers are relatively evenly distributed at any angle in the horizontal direction, and are not densely concentrated in one place. In addition, the fibers are also evenly present inside the structure of the SiO2 aerogel, indicating that the chopped glass fibers are dispersed more evenly.

[0107] Figure 2 This is a scanning electron microscope image of the fiber-reinforced super-hydrophobic SiO2 aerogel paste prepared in Example 1, magnified 10,000 times. Figure 2 It can be seen that the SiO2 gas gel covers the surface of the chopped glass fiber well, the two are closely combined, not in a loose composite state, and the SiO2 gas gel is evenly distributed in all directions of the glass fiber cylinder.

[0108] from Figure 1 , Figure 2 It can be seen from the morphology diagram that in the fiber-reinforced superhydrophobic SiO2 aerogel paste prepared in Example 1, the morphology of the chopped glass fibers has not changed much, and they are still evenly present in the SiO2 aerogel paste in a flat state. It can also be seen that the composite of glass fiber and SiO2 aerogel is good, and the comprehensive performance of the fiber-reinforced SiO2 aerogel paste prepared in this way is greatly improved. This is because the addition of glass fiber does not cause a significant change in the skeleton structure of the SiO2 aerogel, so the excellent performance of the SiO2 aerogel itself is retained, and the presence of glass fiber will greatly improve the mechanical properties of the SiO2 aerogel composite material.

[0109] 2. Characterization of hydrophobic properties

[0110] Figure 3This is a hydrophobic angle picture of the fiber-reinforced super-hydrophobic SiO2 aerogel paste prepared in Example 1 when the coating thickness is 3 mm. The contact angle of the aerogel paste is 128.8°, which is greater than 90°, indicating that the aerogel paste is hydrophobic. The hydrophobicity is generated because during the preparation of the aerogel paste, the SiO2 wet gel glass fiber system is surface-modified with hexamethyldisilazane (HMDZ), and the hexamethyldisilazane reacts with the Si-OH on the surface of the SiO2 aerogel skeleton to obtain the hydrophobic group Si-CH3. Therefore, the obtained fiber-reinforced super-hydrophobic SiO2 aerogel paste is hydrophobic.

[0111] 3. Mechanical properties test

[0112] The fiber-reinforced super-hydrophobic SiO2 aerogel paste after drying in Example 1 was molded according to GB / T 17911-2018 and stretched to test its mechanical properties at a stretching rate of 10 mm / min. The results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the fiber-reinforced superhydrophobic SiO2 aerogel paste prepared in this embodiment has certain tensile properties. SiO2 aerogel itself is a brittle material and is easily broken, but the aerogel paste prepared in this embodiment has good tensile properties and only breaks when the load is close to 120N. On the one hand, this shows that the addition of glass fiber gives the aerogel paste certain mechanical properties. On the other hand, it also shows that the composite condition of SiO2 aerogel and glass fiber is good.

[0113] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an environmentally friendly SiO2 aerogel paste, characterized in that: include: (1) Preparing SiO2 wet gel: dissolving a silicon source in deionized water and stirring to obtain a sodium silicate aqueous solution, then adding urea, imidazole carboxylic acid ionic liquid, functional filler, dispersant, and sunscreen to obtain a mixed solution, stirring the mixed solution, stopping stirring when the mixed solution shows signs of thickening, adding fibers treated with a silane coupling agent, and stirring to obtain SiO2 wet gel with fibers; (2) Polymerization aging: The SiO2 wet gel with fibers is moved to another container for polymerization aging; (3) Solvent replacement: The SiO2 wet gel with fibers after polymerization aging is washed and then subjected to a replacement reaction; (4) Surface modification: The SiO2 wet gel with fibers after the replacement reaction is filtered, the material obtained after the filtration is placed in n-hexane for mechanical stirring, and then a hydrophobic agent is added to perform surface hydrophobic modification to obtain a super-hydrophobic SiO2 wet gel fiber system; (5) Filtration and drying: The superhydrophobic SiO2 wet gel fiber system is filtered and washed with n-hexane, and then dried to obtain a SiO2 gas gel paste.

2. The preparation method according to claim 1, characterized in that: The structural formula of the imidazole carboxylic acid ionic liquid in (1) is: Where R is C 1~10 A straight chain alkane group.

3. The preparation method according to claim 1, characterized in that: The silicon source in (1) is 3.1 model water glass or tetraethyl orthosilicate; the functional filler is TiO2, talcum powder or sepiolite; the dispersant is 602N dispersant or OS-5040 dispersant; the sunscreen is styrene-acrylate copolymer; and the silane coupling agent is KH-560.

4. The preparation method according to claim 1, characterized in that: The fibers in (1) are one or both of glass chopped fibers and ceramic chopped fibers; the fiber length is 2.2 to 3.0 mm.

5. The preparation method according to claim 1, characterized in that: In the (1), by weight, the amount of silicon source is 40 to 100 parts, the amount of deionized water is 160 to 400 parts, the amount of urea is 10 to 20 parts, the amount of carboxylic acid ion liquid is 100 to 200 parts, the amount of functional filler is 5 to 40 parts, the amount of dispersant is 5 to 10 parts, the amount of sunscreen is 0 to 20 parts, and the amount of fiber treated with silane coupling agent is 50 to 100 parts.

6. The preparation method according to claim 1, characterized in that: The polymerization aging temperature in (2) is 70° C. and the time is 8 h.

7. The preparation method according to claim 1, characterized in that: The replacement reaction time in (3) is 16 to 72 hours; the replacement reaction solution is a mixture of anhydrous ethanol and tetraethyl orthosilicate or anhydrous ethanol.

8. The preparation method according to claim 1, characterized in that: The hydrophobic agent in (4) is trimethylchlorosilane or hexamethyldisilazane; the amount of the hydrophobic agent is 0 to 40 parts by weight; and the mechanical stirring speed is 800 r / min.

9. The preparation method according to claim 1, characterized in that: In the step (5), the drying temperature is 60° C. and the drying time is 2 to 6 hours.

10. An environmentally friendly hydrophobic aerogel paste, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Glass fiber reinforced silicon dioxide aerogel composite material and preparation method thereof

    CN101973752B

  • airgel and xerogel composites, processes for their manufacture and their use

    DE4430642A1

  • Process for the production of fiber-reinforced xerogels and their use

    DE4430669A1